Love your enemies: Hãy yêu kẻ thù của bạn - Tran, Van Bien (Khoa Học Công Giáo và Đời Sống, 2022)
“Love your enemies” is the commandment of Jesus. But to “love your enemies” is never easy. In this article, I would like to share 3 ideas to know how to love enemies, which are: First, to love your enemies is to portray the love of God Second, to love your enemies is to forgive them. Third, to love your enemies is to pray for them.